CIVILIZATIONAL BASIS OF ANTHROPOLOGICAL TRANSFORMATIONS - Soghomonyan , G.A. (Modern Psychology, 2019)
In postmodern world anthropological transformations happen by three common civilizational reasons: 1) the transformation of the nature of man, of his physical and mental qualities in connection with the intensive development of the man-made environment, leading to the displacement of all natural in the human by the artificial; 2) the erosion, the weakening and even the disappearance of those social conditions of life that have always been customary for a man in a "traditional" society and constituted a world of its existence; 3) the profound changes of the inner world of man, his values, life orientations due to the omnipresence of the market, the consumer onsets in the life of the society. In analyzing the problem of challenges, which descended upon mankind as a result of technological progress, the author concludes that the construction of the trans-humanist social welfare system will never bring happiness to humanity if the search for such welfare will be conducted outside of the system-preserving traditions and spiritual needs of man.
Keywords: globalization, technocratic society, anthropological crisis, body centric culture, spiritual, tradition.